2012
DOI: 10.1016/s0924-9338(12)75173-8
|View full text |Cite
|
Sign up to set email alerts
|

P-1006 - The role of hypoxia in mental development and in the prevention and treatment of mental disorders: a review

Abstract: The purpose of this review is to trace the trends in studying and applying hypoxia in the field of mental problems. A literature review was conducted using the PubMed database, with a time-frame extending to January 2012. According to the neurodevelopmental model of mental disorders, abnormalities in brain development during pre- and perinatal life lead to psychotic manifestation in adolescence or young adulthood. Studies show that hypoxia plays an important role in almost any risk factor related to brain deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…Other observations and explanations on health effects at higher altitudes include: a) protective effect against certain causes of death due to adaptation to decreased oxygen pressure [3]; b) protective effect against a number of disorders, including psychiatric disorders because of altitude hypoxia [15], which may be more effective if applied intermittently [16]; and c) risk factor for some conditions, as noted above [4][5]. Thus, effects of living at higher altitudes appear to: a) be a mixture of benefits and risks, and b) have different possible explanations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other observations and explanations on health effects at higher altitudes include: a) protective effect against certain causes of death due to adaptation to decreased oxygen pressure [3]; b) protective effect against a number of disorders, including psychiatric disorders because of altitude hypoxia [15], which may be more effective if applied intermittently [16]; and c) risk factor for some conditions, as noted above [4][5]. Thus, effects of living at higher altitudes appear to: a) be a mixture of benefits and risks, and b) have different possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the low level radiation range, cancer rates may actually decrease with increasing amounts of low level radiation, but obviously only to a point, where the radiation becomes high level, and, as previously noted, the cancer rates would be expected to increase with increasing high levels of radiation in a linear fashion. Others contend that radiation risks are linear, and that there is no threshold in the low level radiation range for which ionizing radiation can be considered safe (referred to as the linear non-threshold model) [14].Other observations and explanations on health effects at higher altitudes include: a) protective effect against certain causes of death due to adaptation to decreased oxygen pressure [3]; b) protective effect against a number of disorders, including psychiatric disorders because of altitude hypoxia [15], which may be more effective if applied intermittently [16]; and c) risk factor for some conditions, as noted above [4][5]. Thus, effects of living at higher altitudes appear to: a) be a mixture of benefits and risks, and b) have different possible explanations.…”
mentioning
confidence: 99%
“…Some trials were performed by means of sojourns in the high mountains, by the use of hypobaric chamber and by the use of normobaric hypoxia (74). The results were negligible or insufficiently strong (for schizophrenia) or moderate (for depression).…”
Section: Iht and Its Clinical Applicationsmentioning
confidence: 99%
“…87 Despite the fact that none of the DMPs reported in this study overlapped with genes reported to associate with gestational age, 87 it should be noted that the HumanMethyla-tion27 BeadChip array (Illumina) may be not robust enough to identify all genes associated with gestational age. In addition, birth complications can result in negative outcomes that increase the risk of mental disorders, 88 as well as impact the epigenome. 89 However, information on pregnancy and birth complications was unavailable for our cohort; thus, future studies will be necessary to assess the relation between birth complications, DNA methylation signatures and mental disorders.…”
Section: Discussionmentioning
confidence: 99%